Evolution of a child with Treacher Collins syndrome undergoing physiotherapeutic treatment - Bárbara Gabriela da S. Rodrigues; Juliane Leonardo Oliveira Silva; Pryscilla Gualberto Guimarães; Cibelle Kayenne Martins Roberto Formiga; Fabiana Pavan Viana
AbstractIntroduction Treacher Collins syndrome, or mandibulofacial dysostosis, is a hereditary disorder and is manifested by craniofacial malformations. The incidence is close to one case per 40,000 live births, without relation to gender or race. The infant carrier may present neurological development. This rare syndrome requires documentation of its main clinical and kinetic-functional consequences.Objectives The purpose of this study was to describe the clinical and kinetic-functional findings for a child who has Treacher Collins syndrome and receives treatment in the Physiotherapy Department at the Pestalozzi Association in Goiania, and to present the evolution of motor function and psychomotor development during rehabilitation.Materials and methods The information was obtained through interviews with the mother, and evaluation of the child at nine and eleven months old, using the infant neurological assessment sheet, Inventory Operational Portage (IPO) and Gross Motor Function Measure (GMFM).Results The GMFM showed that the child had a higher trend in the items for lying and rolling, sitting, crawling and kneeling and minor changes in the items for standing, walking, running and jumping. In the IPO, the child progressed in all of the assessed areas: infant stimulation, motor development, socialization, self-care, cognition and language.Conclusion The child showed progress in psychomotor development in accordance with that expected for their age and initial assessment. It is suggested that children with this syndrome be treated by multidisciplinary teams in the first years of life, preventing delays and deviations in development.